Phenomenological Hints from a Class of String Motivated Model Constructions - Hans Peter Nilles (Advances in High Energy Physics)
We use string theory constructions towards the generalisation of the supersymmetric standard model of strong and electroweak interactions. Properties of the models depend crucially on the location of fields in extradimensional compact space. This allows us to extract some generic lessons for the phenomenological properties of the low energy effective action. Within this scheme we present a compelling model based on local grand unification and mirage mediation of supersymmetry breakdown. We analyse the properties of the specific model towards its possible tests at the LHC and the complementarity to direct dark matter searches.